The Role of Setting in Angela Carter’s “Nights at the Circus” - Kamolova Feruza (Universitas Muhammadiyah Sidoarjo, 2022)
Before analyzing setting in the book, we would like to give information about types of setting and how it is important to reveal the events in a particular place. In fiction, setting includes the time, location, and everything in which a story takes place, and initiates the main backdrop and mood for a story. Setting has been referred to as story world http://en.wikipedia.org/wiki/Setting_(fiction) - cite_note-0 or milieu to include acontext (especially society) beyond the immediate surroundings of the story. Elements of setting may include culture, historical period, geography, and hour. Along with plot, character, theme, and style, setting is considered one of the fundamental components of fiction.